SAT0093 Success-1 in osteoarthritis: celecoxib demonstrates similar efficacy to the conventional nsaids, diclofenac and naproxen, in patients with osteoarthritis treated in 39 countries in 6 continents. (1st June 2001) - Singh, G; Goldstein, J; Fort, J; Bello, A; Boots, S
Abstract : Background: The SUCCESS-1 trial is the largest controlled study comparing celecoxib and NSAIDs. This long-term trial was intended to closely parallel clinical practice in a variety of worldwide settings to assess the overall efficacy, tolerability, and safety of celecoxib and NSAIDs with a large group of diverse physicians. Objectives: This study compared the efficacy, safety, and tolerability of celecoxib 200 and 400 mg per day and the most commonly prescribed NSAIDs in 39 countries in the treatment of the signs and symptoms of osteoarthritis (OA) of the knee, hip, and hand. Methods: The SUCCESS-1 in OA trial is a large double-blind, randomised study conducted in patients from 1, 142 centres in Europe and South Africa, Asia, Latin America, and the US and Canada. Patients were treated for 12 weeks using celecoxib (200 or 400 mg/d) and the most common regimens of NSAIDs (naproxen 1000 mg/d in US and Canada and diclofenac 100 mg/d in all other countries). Assessments of arthritis efficacy were performed by country or region. Safety and tolerability were assessed globally. Results: Of the 13, 194 intent-to-treat patients, the mean age was 62 years, and the majority were female (76%) and caucasian (80%). Patients in each group had comparable baseline aspirin use and history of upper GI bleeding. Arthritis assessments were based on mean changes in baseline arthritis pain by VAS and night pain at week 12. Data is presented from European countries/regions. No significant differences between celecoxib 200 mg/day and celecoxib 400 mg/day compared to diclofenac 100 mg/day were observed. In addition, celecoxib 200 mg/day and 400 mg/day were similar in efficacy. Comparable efficacy between celecoxib and NSAIDs was also demonstrated in other countries/regions that participated in the study. Conclusion: This study adds substantially to the available efficacy data on celecoxib. It expands the data globally on the efficacy of celecoxib to various settings that closely follow local clinical practice. Celecoxib demonstrated similar efficacy to the most commonly prescribed regimen of diclofenac in the treatment of OA. Sponsored by Pharmacia Corporation and Pfizer Inc.